Islamization of contemporary knowledge and reform of education and curriculum - Ssekamanya, Siraje Abdallah; Hashim, Rosnani (2012)
Islamization is normally defined as a process to Islamize in term of faith, belief or worldview and thus it is applied to human beings. In this sense it is similar to the calling to Islam or da’wah. However in the context of our discussion, Islamization is further extended to refer to the process of education, therefore including its philosophy, its curriculum which encompasses objectives, knowledge, methods and assessment. Islamization or da’wah, is a process that began with the mission of the Prophets but in the context of Islam, it began with the Prophet Muhammad s.a.w. and his success is well recorded in history and we became part of that evidence. Philosophically, education in the Islamic tradition cannot be separated from the inculcation of faith and the realization of one’s abdship and vicegerency. Rarely did one speak of the term Islamization of education or curriculum. This paper is an attempt to explain this new phenomenon and its necessity. It also attempts to examine the educational reforms that have taken place to achieve the goals of Islamization of education as well as the experience of Islamization at IIUM.